Direct And Indirect Effect Of Marketing Capabilities On The Performance Of MSMEs - Nur Laili Fikriah; Mega Noerman Ningtyas; Ikhsan Maksum (Jurnal Ekonomi, 2024)
This research aims to determine whether the use of social media can improve marketing capabilities and performance of MSMEs, marketing capabilities improve MSME performance and the mediating role of marketing capabilities of the use of social media and MSME performance. The dimensions for measuring social media use are marketing, relationships and services, information search, cost-effectiveness, and Compatibility. The quantitative research approach involves 230 respondents who are MSME actors in Indonesia. The hypothesis analysis method for this research uses the Partial Least Square-Structural Equation Modeling (SEM-PLS) method. The findings of this research indicate that the use of the social media platforms WhatsApp, Instagram, Facebook, TikTok, and Telegram, as well as the fifth dimension used to measure social media use, also influences social media use. The results of marketing capability mediating between social media use and MSME performance have a positive and mediating influence.